Crescimento, desenvolvimento e produção de brócolis de cabeça única - Trevisan, Jorge Nadir (2013)
Single-head broccoli (Brassica oleracea L. var.italica Plenk) is one of the vegetables with the latest introduction to Brazil and its cultivation has increased gradually over the past decades. This crop has potential to diversify vegetable production in Rio Grande do Sul central area as an economic and horticultural alternative to tobacco growing which widespread among local farmers, as well as to supply regional produce market. The aim of this work was to study growth, development and yield using data generated in two experiments with single-head broccoli hybrids grown in two seasons. The experiments were conducted at the Universidade Federal de Santa Maria(UFSM), Santa Maria, RS, using Legacy and BRO 68 hybrids transplanted on march 22, 2011 and july 30, 2011. We evaluated morphological and productive variables as well as thermal time from transplanting through to the first flower opening. Adjusted growth curves by the cosine model, were determined measuring the length and width of the leaf blade to estimate leaf area, and the variance was analysed in factorial schemes. The model of growth and development of the cosine provided a good fit with the coefficient of determination higher than 70%. Concerning growth, leaf area differed between seasons and between the hybrids in the second season; number of leaves between hybrids in both seasons; component variables of head height, diameter and head green phytomasses, florets and stem apex, between the hybrids in the first season. The thermal time for hybrid Legacy in the first season was 1479.9 degree-days and in the second season was 1285.5 degree-days. The thermal time for hybrid BRO 68 in the first season was 1423.1 degree-days and second season was 1172.8 degree-days. The best model for estimating leaf area was: leaf area = - 0.006981 + 0.000878403 x W1,5, using the width of the leaf for hybrid BRO 68, whereas for 'Legacy ', was: leaf area = 0.0174307 + 0.00000249604 x (L x W)1.5, involving the product of leaf length and width. There was interaction between hybrids and seasons for head green phytomass. Legacy‟ was latest in both seasons and the most productive in the first season, with an average head phytomass of 755.72 g head-1. Both hybrids had the highest average weights in the second season, with 864.43 g head-1 and 862.62 g head-1 for 'BRO 68' and 'Legacy', respectively.